Cyber Risk Surveillance : A Case Study of Singapore - Goh, Joseph (IMF Working Papers; Working Paper ;, 2020)
Cyber risk is an emerging source of systemic risk in the financial sector, and possibly a macro-critical risk too. It is therefore important to integrate it into financial sector surveillance. This paper offers a range of analytical approaches to assess and monitor cyber risk to the financial sector, including various approaches to stress testing. The paper illustrates these techniques by applying them to Singapore. As an advanced economy with a complex financial system and rapid adoption of fintech, Singapore serves as a good case study. We place our results in the context of recent cybersecurity developments in the public and private sectors, which can be a reference for surveillance work.